Keratoprostheses in silicone oil-filled eyes: long-term outcomes. Issue 6 (18th July 2018) - Iyer, Geetha; Srinivasan, Bhaskar; Agarwal, Shweta; Pattanaik, Ruchika; Rishi, Ekta; Rishi, Pukhraj; Shanmugasundaram, Shanmugasundaram; Natarajan, Viswanathan
Abstract : Purpose: To analyse the functional and anatomical outcomes of different types of keratoprostheses in eyes with retained silicone oil following vitreoretinal surgery. Methods: Retrospective chart review of patients operated with any type of permanent keratoprosthesis (Kpro) in silicone oil-filled eyes between March 2003 and June 2017 were analysed. Results: 40 silicone oil-filled eyes underwent keratoprostheses, of which 22 were type 1 and 18 were type 2 Kpros (Lucia variant—nine, modified osteo odonto kerato prosthesis (MOOKP)—four, Boston type 2—three and osteoKpro—two) with a mean follow-up of 61.54, 42.77, 45.25, 25 and 37 months, respectively. Anatomic retention of the primary Kpro was noted in 33 eyes (82.5%). A best-corrected visual acuity of better than 20/200 and 20/400 was achieved in 26 (65%)+32 (80%) eyes. Retroprosthetic membrane (RPM) was the most common complication noted in 17 eyes (42.5%). Perioptic graft melt was noted in 4 of 22 eyes of the type 1 Kpro (2 (10.5%) without associated ocular surface disorder (OSD)) and in 1 eye each of Boston and Lucia type 2 Kpro. Laminar resorption occurred in one eye each of the MOOKP and OKP groups. Endophthalmitis and glaucoma did not occur in any eye. Conclusion: Appropriately chosen keratoprosthesis is a viable option for visual rehabilitation in eyes post vitreoretinal surgery with retained silicone oil-induced keratopathy not amenable to conventional penetrating keratoplasty. Kpro melt among type 1 Kpro did not occur in 89.5% eyes without associated OSD (19 of 22 eyes), despite the lack of aqueous humour and presence of RPM (4 eyes), two factors considered to play a significant role in the causation of sterile melts. Of interest to note was the absence of infection in any of these eyes. The possible protective role of oil from endophthalmitis is interesting, though yet to be ascertained.